Gambaran Pengetahuan Remaja Putri tentang Faktor Penyebab Anemia di SMA Adhyaksa 1 Kota Jambi - Julaecha, Julaecha; Nurita, Suci Rahmani (3031-8572, 2024)
Anemia is still a health problem, especially in developing countries, an estimated 30% of the world's population suffers from anemia, especially adolescent girls. Many factors cause anemia such as lack of iron, folic acid and vitamin B12, abnormal menstrual cycles, food management and the body's need for iron. To find out the factors that cause anemia in young women, research was conducted on the description of knowledge and factors that influence the occurrence of anemia. The research method used was descriptive to determine the description of the factors that influence anemia. The population in this study was 229 people, the sample was 35 people, the sampling technique was random sampling, the instrument for measuring knowledge used a questionnaire, the data collected was analyzed univariately. The results showed that the majority of 21 people (60%) had sufficient knowledge of young women, (14.28%) had good knowledge, 9 people (25.71%) had poor knowledge. 32 people (91.4%) of young women did not consume blood supplement tablets and only 3 people (8.57%) consumed blood supplement tablets regularly. Lack of compliance among teenagers in consuming blood-added tablets makes it possible for teenagers to feel that they do not experience symptoms of anemia and when consuming blood-added tablets they feel nauseous, the medicine smells fishy. The conclusion of the research is that the picture of adolescent girls regarding anemia is due to the knowledge factor so that the level of adherence of adolescents to consuming blood supplement tablets is low, it is necessary to provide continuous education and check Hb levels regularly.